2003
DOI: 10.1016/s0990-7440(03)00084-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of common carp sperm

Abstract: Experiments were carried out to investigate the effect of five extenders (sucrose, glucose, fructose, KCl and a saline carp sperm extender) and two cryoprotectants (dimethyl-sulfoxide (DMSO) and methanol) on the cryopreservation of common carp sperm. Freezing of sperm using glucose extender and methanol as cryoprotectant resulted in the highest post-thaw motility, fertilization as well as hatching rates (63 ± 9%, 74 ± 15% and 67 ± 17% vs. 87 ± 5%, 84 ± 14% and 69 ± 14% using fresh sperm, respectively). In gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 17 publications
6
57
0
2
Order By: Relevance
“…According to Ashwood-Smith (1980), methanol is in capability of penetrating to the cells with extreme rapidity. In addition, Horvath et al (2003) also reported highest fertilization and hatching rates in common carp eggs inseminated with sperm frozen with glucose and fructose based extenders that's containing methanol as internal permeable cryoprotectant.…”
Section: Discussionmentioning
confidence: 89%
“…According to Ashwood-Smith (1980), methanol is in capability of penetrating to the cells with extreme rapidity. In addition, Horvath et al (2003) also reported highest fertilization and hatching rates in common carp eggs inseminated with sperm frozen with glucose and fructose based extenders that's containing methanol as internal permeable cryoprotectant.…”
Section: Discussionmentioning
confidence: 89%
“…Significant inter-species variations as well as significant within-species differences in cryoprotectant effectiveness have been reported in fish spermatozoa (Alavi et al 2012). For example, 8-10% DMSO + P was associated with the highest sperm motility after freeze/thaw in tench ; MET was reported to be the optimal cryoprotectant for sperm of roach Rutilus rutilus, bream Abramis brama, silver bream Blicca bjoerkna, and barbel Barbus barbus (Urbanyi et al 2006); and DMSO has been recommended for common carp (Horvath et al 2003). The tested cryoprotectant treatments of tench GC showed no significant differences, indicating high stability of GC in cryoprotectants.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm (200 μl) mixed with a cryopreservation medium (200 μl cryoprotectant, 1600 μl diluent) in a ratio of 1:9 (Horváth et al, 2003;Urbányi et al, 2006) was pipetted into individually marked 0.5-ml straws after 3 minutes of equilibration time. Samples were cryopreserved in a polystyrene box filled with liquid nitrogen.…”
Section: First Experimentsmentioning
confidence: 99%
“…After the freezing process straws were placed into liquid nitrogen and stored there until being used. Thawing was carried out in a 40˚C water bath for 13 seconds (Horváth et al, 2003;Horváth et al, 2005). After thawing sperm motility was examined with the same method as described at fresh sperm.…”
Section: First Experimentsmentioning
confidence: 99%